Multiple P–T–d–t paths reveal the evolution of the final Nuna assembly in northeast Australia. (15th June 2020) - Volante, Silvia; Pourteau, Amaury; Collins, William J.; Blereau, Eleanore; Li, Zheng‐Xiang; Smit, Matthijs; Evans, Noreen J.; Nordsvan, Adam R.; Spencer, Chris J.; McDonald, Brad J.; Li, Jiangyu; Günter, Christina
Abstract: The final assembly of the Mesoproterozoic supercontinent Nuna was marked by the collision of Laurentia and Australia at 1.60 Ga, which is recorded in the Georgetown Inlier of NE Australia. Here, we decipher the metamorphic evolution of this final Nuna collisional event using petrostructural analysis, major and trace element compositions of key minerals, thermodynamic modelling, and multi‐method geochronology. The Georgetown Inlier is characterised by deformed and metamorphosed 1.70–1.62 Ga sedimentary and mafic rocks, which were intruded by c . 1.56 Ga old S‐type granites. Garnet Lu–Hf and monazite U–Pb isotopic analyses distinguish two major metamorphic events (M1 at c . 1.60 Ga and M2 at c . 1.55 Ga), which allows at least two composite fabrics to be identified at the regional scale— c . 1.60 Ga S1 (consisting in fabrics S1a and S1b) and c . 1.55 Ga S2 (including fabrics S2a and S2b). Also, three tectono‐metamorphic domains are distinguished: (a) the western domain, with S1 defined by low‐ P ( LP ) greenschist facies assemblages; (b) the central domain, where S1 fabric is preserved as medium‐ P ( MP ) amphibolite facies relicts, and locally as inclusion trails in garnet wrapped by the regionally dominant low‐ P amphibolite facies S2 fabric; and (c) the eastern domain dominated by upper amphibolite to granulite facies S2 foliation. In the central domain, 1.60 Ga MP– medium ‐T (MT) metamorphism (M1) developed within the staurolite–garnet stability field, with conditions ranging from 530 – 550°C at 6 – 7 kbar (garnet cores) to 620 – 650°C at 8 – 9 kbar (garnet rims), and it is associated with S1 fabric. The onset of 1.55 Ga LP– high‐ T ( HT ) metamorphism (M2) is marked by replacement of staurolite by andalusite (M2a/D2a), which was subsequently pseudomorphed by sillimanite (M2b/D2b) where granite and migmatite are abundant. P–T conditions ranged from 600 to 680°C and 4–6 kbar for the M2b sillimanite stage. 1.60 Ga garnet relicts within the S2 foliation highlight the progressive obliteration of the S1 fabric by regional S2 in the central zone during peak M2 metamorphism. In the eastern migmatitic complex, partial melting of paragneiss and amphibolite occurred syn‐ to post ‐ S2, at 730–770°C and 6–8 kbar, and at 750–790°C and 6 kbar, respectively. The pressure–temperature–deformation–time paths reconstructed for the Georgetown Inlier suggest a c . 1.60 Ga M1/D1 event recorded under greenschist facies conditions in the western domain and under medium‐ P and medium‐ T conditions in the central domain. This event was followed by the regional 1.56–1.54 Ga low‐ P and high‐ T phase (M2/D2), extensively recorded in the central and eastern domains. Decompression between these two metamorphic events is ascribed to an episode of exhumation. The two‐stage evolution supports the previous hypothesis that the Georgetown Inlier preserves continental collisional and subsequent thermal perturbation associated with granite emplacement.